مدخل للإدارة والتسيير الرياضي - بطاط ، نورالدين (Mohamed Boudiaf University of M'Sila, 2023)
الملخص : بالعربية : وفي الوقت الذي حظيت به الرياضة في مختلف المؤسسات والمنظمات الوطنية، باهتمام رسمي و شعبي، ومع تطور المستويات الفنية من خلال البطولات والمسابقات، ومن ضمن تلك الخطوات، التي تمثلت في إنشاء العديد من كليات التربية البدنية والرياضية، وتوسع القطاعات الاهلية من أندية ومراكز للياقة البدنية، وما تحتاجه هذه الاعمال من كفاءات مؤهلة قادرة على تطوير الاداء الاداري، فقد برزت الحاجة إلى تحديد الاسس والقواعد لهذا العمل الاداري الذي هو ابرز عوامل النجاح، ومن دون شك فإن الادارة بصفة عامة والادارة الرياضية بصفة خاصة هي الكفيلة بوضع هاته الاسس والقواعد المتمثلة في عمليتها الادارية من التخطيط والتنظيم وتوجيه ورقابة ووفقا لمبادئها العامة وحسب الاهداف المرجوة منها، والتي تحدد حسب حالة كل منشأة أو منظمة، في سبيل تطوير الاداء الإداري. Searchlight in English At a time when sports in various national institutions and organizations received official and popular attention, and with the development of technical levels through tournaments and competitions, and among those steps, which were the establishment of many colleges of physical education and sports, and the expansion of private sectors of clubs and fitness centers physical, What these businesses need are qualified competencies capable of developing administrative performance. The need has emerged to define the foundations and rules for this administrative work, which is the most prominent factor in success. Without a doubt, administration in general and sports administration in particular are responsible for establishing these foundations and rules represented in its administrative process. Of
Keywords: مدخل للتسيير الرياضي; مدخل للإدارة الرياضية; لمنظمات الوطنية